2014
DOI: 10.1097/psy.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Lung Cancer Care of Elderly Patients With Schizophrenia

Abstract: Objective Cancer mortality is higher in individuals with schizophrenia, a finding that may be due, in part, to inequalities in care. We evaluated gaps in lung cancer diagnosis, treatment, and survival among elderly individuals with schizophrenia. Methods The Surveillance, Epidemiology, and End Results (SEER) database linked to Medicare records was used to identify primary non-small cell lung cancer (NSCLC) patients ≥66 years of age. Lung cancer stage, diagnostic evaluation, and rates of stage-appropriate tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…Where all cancers and/or all mental illnesses are examined together, the different stage distribution for different cancers and mental illnesses may be obscured, resulting in no apparent relationship (for example [7]). Differences in findings for the same mental illness diagnosis (e.g., schizophrenia) are likely to relate to the cancer and the health system setting -for example, the finding of earlier lung cancer diagnosis in Medicare patients with schizophrenia than others [20] suggests that these patients undergo a high degree of surveillance of the type likely to pick up lung cancer (likely chest x-rays) in the Medicare system.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Where all cancers and/or all mental illnesses are examined together, the different stage distribution for different cancers and mental illnesses may be obscured, resulting in no apparent relationship (for example [7]). Differences in findings for the same mental illness diagnosis (e.g., schizophrenia) are likely to relate to the cancer and the health system setting -for example, the finding of earlier lung cancer diagnosis in Medicare patients with schizophrenia than others [20] suggests that these patients undergo a high degree of surveillance of the type likely to pick up lung cancer (likely chest x-rays) in the Medicare system.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies which have examined the role of cancer stage at diagnosis in survival disparities for people with history of mental illness have produced conflicting findings, with some studies finding that mental illnesses are associated with late diagnosis [10], while others finding an association with early diagnosis [20], or no association [7]. Preexisting illness (including mental illness) can influence the stage at which cancers are diagnosed in a variety of ways, sometimes overshadowing cancer symptoms resulting in late diagnosis, but in other cases leading to increased surveillance resulting in earlier cancer diagnosis, depending on factors such as the severity of the illness, the type of cancer and the health system context [21].…”
Section: Discussionmentioning
confidence: 98%
“…A study of Surveillance, Epidemiology and End Results‐Medicare‐linked data showed that individuals with mental illness (defined as mood disorders, psychotic disorders, dementia, substance abuse and dependence disorders, and other) and colon cancer are more likely to have unstaged colon cancer or a diagnosis of colon cancer at autopsy . Another Surveillance, Epidemiology and End Results‐Medicare analysis revealed that patients with schizophrenia and nonsmall cell lung cancer are less likely to have appropriate evaluation . A study of Swedish adults with schizophrenia who died of cancer showed that those individuals were less likely to have a cancer diagnosis before death .…”
Section: Treatmentmentioning
confidence: 99%
“…The articles were Updates in Psychosomatic Medicine related to 15 subspecialties: cardiac psychiatry, [4][5][6][7][8][9] collaborative care/integrated behavioral health, 10,11 emergency psychiatry, 12,13 HIV psychiatry, [14][15][16][17][18][19][20] neuropsychiatry, 21-31 pediatric psychosomatic medicine, 32-36 psychodermatology, [37][38][39][40][41][42][43][44][45] psychonephrology, 46-55 psycho-oncology and palliative care, [56][57][58][59][60][61][62][63][64] serious mental illness, [65][66][67][68][69][70][71][72] somatic symptom disorders, 73 suicide, 74-78 transplant psychiatry, [79][80][81][82][83][84]…”
Section: Resultsmentioning
confidence: 99%